1981
DOI: 10.1111/j.1151-2916.1981.tb09602.x
|View full text |Cite
|
Sign up to set email alerts
|

Ion Exchange of Soda‐Lime Glass with Univalent Cations

Abstract: Fhdeld‐assisted and ordinary diffusion ion exchange of K+, Rb+hd Cs+, and Ag+ from nitrate salts with Na+ in soda‐lime glass tubes were investigated between 700 and 735 K by application of various currents between 0 and 20.0 mA. An analysis of the field‐assisted process with both a forward and a reverse field allowed calculation of the conductivity of the exchanged layer from the change of potential difference with time. Good agreement with experiment was found in both directions but anomalously high conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…It has been shown before that the obtained values are in reasonable agreement with other published data (Pask and Parmelee, 1943;Shaisha and Cooper, 1981;Gonella et al, 1998;Liu and Pun, 2004;Karlsson et al, 2010bKarlsson et al, , 2012. In a practical consideration, the effective diffusion coefficient represents the efficiency of the ion-exchange reaction, in other words, the rate of the ion exchange.…”
Section: Methodssupporting
confidence: 82%
“…It has been shown before that the obtained values are in reasonable agreement with other published data (Pask and Parmelee, 1943;Shaisha and Cooper, 1981;Gonella et al, 1998;Liu and Pun, 2004;Karlsson et al, 2010bKarlsson et al, , 2012. In a practical consideration, the effective diffusion coefficient represents the efficiency of the ion-exchange reaction, in other words, the rate of the ion exchange.…”
Section: Methodssupporting
confidence: 82%
“…Refractive-index profiles were generated from measured n,E data using the WIG3 method (Chiang 1985). Shaisha andCooper 1981, Honkanen andTervonen 1988) that information concerning the relative mobilities of the sodium and silver ions can be obtained by analysing the change in the electrical conductivity of the glass during diffusion of the silver. This has previously been achieved by monitoring the current passing through the sample as a function of time during diffusion with a constant applied potential (Viljanen andLeppihalme 1981, Honkanen andTervonen 1988) or by monitoring the voltage developed across the sample as a function of time during a constant-current process (Shaisha and Cooper 1981).…”
Section: Diffusion and Optical Analysismentioning
confidence: 99%
“…Shaisha andCooper 1981, Honkanen andTervonen 1988) that information concerning the relative mobilities of the sodium and silver ions can be obtained by analysing the change in the electrical conductivity of the glass during diffusion of the silver. This has previously been achieved by monitoring the current passing through the sample as a function of time during diffusion with a constant applied potential (Viljanen andLeppihalme 1981, Honkanen andTervonen 1988) or by monitoring the voltage developed across the sample as a function of time during a constant-current process (Shaisha and Cooper 1981). While, in principle, these appear to be straightforward measurements, it is necessary to eliminate secondary effects when using solid (as opposed to molten salt (Shaisha and Cooper 1981)) back contacts.…”
Section: Diffusion and Optical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…2 and 3 are considered to be the expansion of Al-O-Si network of mother glass due to the introduction of large foreign ions, and the following slight decreases during annealing are considered to be the shrink of Al-O-Si network due to certain atomic adjustment. Previously, Shaisha et al 20 reported that Ag Na ion exchange induces a relatively small compressive stress on the glass surface compared with other alkali ion-pairs because of the small difference of the ionic radius between Ag and Na . This difference of the ionic radius would increase the volume of mother glass.…”
mentioning
confidence: 99%